(untitled) (Revista Contexto & Saúde, 2023)
To understand the articulation of care between the Psychosocial Care Center for alcohol and other drugs and the Family Health Strategy, which makes it possible to propose strategies that can improve articulation/collaboration in an interdisciplinary perspective among service professionals. This is a qualitative study, with a descriptive-exploratory nature, in two Primary Health Care Units and a Psychosocial Care Center for alcohol and other drugs, in the city of Horizonte, which is part of the metropolitan region of Fortaleza, Ceará. The study took place between March 2021 and July 2022, with the participation of 15 professionals, where the information collected was given by sending a semi-structured script via google docs, with content analysis being applied to the construction of the empirical categories analyzed according to the specific literature of this thematic field. The information collected shows that there are weaknesses in the construction of work from the perspective of the health care network. Such fragility is due to failures in the production and continuity of permanent education processes in mental health, absence of a schedule of matrix actions, fragility of referral and counter-referral processes, impacting both the care provided and the management and co-responsibility of care. It is necessary to strengthen both the National Mental Health Policy and the Permanent Education in Health, so that the articulation between teams can be reconstructed in a fluid way